Group portrait of the attendees of the 25th Annual Northern California Hi - Y Older Boys Conference in San Jose, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the 25th Annual Northern California Hi - Y Older Boys Conference, held February 8-10, 1929 in San Jose, California. The image shows several boys holding up signs and flags denoting the area, city, or county of their local Hi - Y chapter.